Makna Simbol Komunikasi Dalam Upacara Adat Keboan Di Desa Aliyan Kabupaten Banyuwangi - Lestari, Tanty Dwi; Sugiarica Joni, I Dewa Ayu; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2017)
ABSTRACT Traditional ceremonies Keboan is one of the traditional ceremonies conducted by the community tribe Osing, precisely in the village of Aliyan, District Rogojampi, Banyuwangi. Traditional ceremonies Keboan which is very closely linked to agriculture. Ceremonies Keboan is usually carried out once a year on the Month Suro (According to the Javanese calendar). This study aims to determine the meaning of the symbols communication contained in the overall ceremonies Keboan. This type of research is descriptive qualitative method, with the theory semiotic and interactionism symbolic, where researchers will provide an overview of the procession and the symbolic meaning of the message contained in the traditional ceremonies Keboan. The data is obtained by interview, direct observation and documentation study. The technique of analyzing the data that used in this research through several steps that was data reduction, data presentation and conclution. Based on the results of research in traditional ceremonies Keboan, each of the stages in this event contains many symbols of communication. In the research the symbols in this event is more prevalent in tribute provided, including there is a beras kuning, tumpeng panca warna, kinangan, kembang setaman, peras, miniature hewan-hewan sawah, and dawet. Meaning of tributes are largely represented a hope society Aliyan to God. The conclusion of this research is ceremonies Keboan is one of the legacy ancestral cultural which until now still be preserved. The traditional ceremony Keboan still kept until today is none other than as a form of reverence to ancestral Aliyan village, and as a form of preservation of culture who want to keep running. Keywords: Meaning Symbols, Semiotics, Interactionism Symbolic, Ceremonies Keboan